Augmented reality-supported rod bending in multilevel spinal fusion using the ADVISE Software - Antes, Sebastian; Moringlane, Rene; Eckardstein, Kajetan L. von (World neurosurgery, 2023)
Background - One of the most common reasons for poor patient outcomes and revision surgery in spinal fusion is hardware failure. Screw loosening or pullout occurs in up to one-quarter of all cases. It is known that even small screw-rod misalignments can cause significant mechanical overloads during rod fixation, which can result in hardware failure. To address this crucial surgical step, a novel augmented reality-assisted software was developed to generate custom rod templates that are precisely adapted to the individual patient. - Methods - The novel software, which runs on a tablet, is used in spinal fusion surgery and is based on the use of a specific pedicle screw system, in which the polyaxial screw heads are connected to detachable guides. These guides can be recognized by the tablet camera and a light detection and ranging scanner. This image information is processed to determine the spatial positions of the screw heads and to calculate an ideally fitting rod template. - Results - The calculated rod template is displayed in a 1-to-1 scale on the tablet screen. This template is used to cut and bend the rods of the pedicle screw system. Finally, the custom bent rod can be inserted into the screw heads without tension. - Conclusions - The augmented reality-assisted software is intended to give surgeons access to patient-specific intraoperative real-time data, helping them in bending rods that are more precisely adapted to the individual patient compared with the freehand technique.